Anatomy of Treason - Zarankaitė, Toma (Lietuvos istorijos studijos, 2017)
About the thesis of Andrėjus Ryčkovas “The concept of treason against the Grand Duke of Lithuania from the end of the 13th century to the mid-16th century”